2012
DOI: 10.1055/s-0032-1311759
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Imaging of the Hand and Wrist Using 3-T MRI

Abstract: The prevalence of osteoarthritis of the hand and wrist is high, and a thorough assessment of even subtle cartilage injuries is necessary before surgical interventions. Although magnetic resonance imaging (MRI) has been established as an important diagnostic tool for the evaluation of hand and wrist disorders, the focus has been on the assessment of the triangular fibrocartilage complex, tendons, ligaments, and the detection of avascular necrosis or occult fractures rather than on cartilage imaging. 3-T MR syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 67 publications
1
9
0
1
Order By: Relevance
“…In the patient group, the morphological sequences were evaluated regarding the presence of visible cartilage damage. Cartilage damage was defined as a focal superficial or deep defect, substantial thinning of the entire layer, or focal swelling with irregularity and edema corresponding to modified Noyes grades 1–3 cartilage damage . Full thickness Noyes grade 4 lesions were not analyzed due to lack of cartilage.…”
Section: Methodsmentioning
confidence: 99%
“…In the patient group, the morphological sequences were evaluated regarding the presence of visible cartilage damage. Cartilage damage was defined as a focal superficial or deep defect, substantial thinning of the entire layer, or focal swelling with irregularity and edema corresponding to modified Noyes grades 1–3 cartilage damage . Full thickness Noyes grade 4 lesions were not analyzed due to lack of cartilage.…”
Section: Methodsmentioning
confidence: 99%
“…We used a sequence protocol similar to that already implemented in the knee and wrist . Besides the study sequences for dGEMRIC, the routine imaging protocol included a cartilage‐sensitive, proton density‐weighted turbo spin‐echo sequence with fat saturation (PDfs) for morphological correlation and exclusion of cartilage defects. Imaging parameters for the PDfs at the wrist were echo time / repetition time (TE/TR) 26/2,370 msec, slice thickness (ST) 2 mm, and acquisition time (TA) 2:06 min, and at the knee were TE/TR 25/3,310 msec, ST 3 mm, and TA 2:56 min.…”
Section: Methodsmentioning
confidence: 99%
“…Normal cartilage was defined as a visually normal cartilage signal on all sequences as well as preserved cartilage thickness with an intact surface and absence of intrachondral signal alterations . Cartilage damage was defined as a focal superficial or deep defect, substantial thinning of the entire layer, or focal swelling with irregularity and edema corresponding to the modified Noyes score . All MRI examinations were randomized, and identifying variables, such as the patient's name, were removed.…”
Section: Methodsmentioning
confidence: 99%
“…It is noteworthy that most of the MRI studies reported so far have been conducted using a conventional magnetic field, i.e., 1.5T but a few studies have clearly indicated that MRI investigations at higher field, e.g., 3T could provide a better signal/noise ratio and a more accurate identification of certain anatomical structures [16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%